Своєрідність спогадового дискурсу Миколи Руденка - Черкашина, Т. (Філологічний дискурс, 2017)
Статтю присвячено дослідженню мемуарно-автобіографічного
дискурсу Миколи Руденка. На прикладі твору «Найбільше диво –
життя» розкривається своєрідність спогадового мислення митця.
Докладно аналізується структура твору, особливості внутрішньої
організації текстової канви. Закцентовано увагу на психологічному
автопортретові письменника, оприявленому на сторінках твору, на
трансформації внутрішнього Я спогадовця. Простежено поступове
розширення особистого простору письменника, що призвело до зміни
світоглядних уявлень Миколи Руденка. Окремої дослідницької уваги
надано вивченню філософемно-екзистенційного дискурсу твору
«Найбільше диво – життя», зокрема проаналізовано відтворення
мотивів усепрощення недругів і ворогів, фатуму, Божого провидіння. The article is devoted to the study of memoire-autobiographical discourse by
Mykola Rudenko. By the example of the memoire works «The Greatest Miracle is
Life» we reveal the particularities of the memoire and autobiographical thinking of
the writer. The structure of this work, the features of the internal organization of the
text canvas are analyzed too. The attention is focused on the psychological
autoportrait of the writer, shown on the pages of the works, on transformation of the
inner I of the memoirist. In the article it is traced the gradual extension of the
personal space of the writer that led to a change in philosophical views of Mykola
Rudenko. The special research attention is given to the study of the philosophical
and existential discourse of the memoire works «The Greatest Miracle is Life», in
particular, we analyzed the representation of the motive of the forgiveness of the foes
and the enemies, the one of destiny and God’s Providence.